Makna Simbolik Tradisi Jolen Sebagai Pandangan Hidup Adiluhung Masyarakat Desa Somongari Kabupaten Purworejo - Margaretha Rizky Christiana; Kuncoro Bayu Prasetyo (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2026)
The Jolen tradition is a cultural practice of the people of Somongari Village, Kaligesing District, Purworejo Regency, which reflects communal life and is rich in symbolic and moral values. This tradition not only functions as a form of earth alms and expression of gratitude for durian and mangosteen harvests, but also acts as social and cultural capital that strengthens community solidarity. This study aims to analyze the process of implementing the Jolen tradition and to examine the symbolic meanings and moral values within the community. This study uses a qualitative approach with descriptive methods. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing, with validity tested through triangulation. The data were obtained from four informants: the Kuncen, Jolen organizers and performers, cultural staff of the Purworejo Regency government, and the Dewi Sri performer (2015). The results show that the Jolen tradition is carried out through several stages, including preparation, procession (carnival), and closing all involving active community participation. This tradition contains various symbolic meanings reflected in cultural elements, including values of gratitude, religiosity, respect for ancestors, mutual cooperation, togetherness, justice, and harmony with nature. These values function as moral guidelines that shape community behavior and social relations. The Jolen tradition not only represents local cultural heritage but also plays an important role in maintaining and strengthening social cohesion in the midst of contemporary social dynamics.